Contraception the answers you've been looking for - Briggs, Paula 1964- (Cambridge University Press, 2023)
Choosing the right method of contraception can be confusing: you need to consider your lifestyle, personal preference, any health conditions you might have, and how effective each method is at preventing pregnancy. Discussing options with your doctor may seem daunting, and information on social media can be misinformed and overwhelming. This handy guide, written by two experts in Sexual and Reproductive Health, will answer all your questions about contraception, helping you decide what works best for you. The authors walk you through every method of contraception, with information on how it works, how to use it correctly and how effective it is. The authors also explain how and when conception can occur during the menstrual cycle, how life stage can affect your choice, and how hormonal contraception can be used to help other health conditions. From the pill to the condom and everything in between, pick what's right for you.